PERLINDUNGAN DAN PENEGAKAN HAK ASASI MANUSIA BAGI ETNIS ROHINGYA YANG TIDAK MEMILIKI KEWARGANEGARAAN MENURUT HUKUM INTERNASIONAL - Yolla .; Aji Wibowo (Fakultas Hukum Universitas Tarumanagara, 2018)
The Rohingya are a largely Muslim ethnic minority that mostly resides in Rakhine, Myanmar. They have lived for centuries in Myanmar region with Buddhist majority, however, they are still not considered as one of Myanmar’s 135 official ethnic groups and their citizenship’s rights have been denied since 1982, which consequently rendering them stateless. Shortly after the 1962 military coup in Myanmar, things had changed dramatically for the Rohingya people. The new citizenship law which has been passed in 1982 was clearly a discrimination law towards the Rohingya people due to its over-burdensome requirements to become a citizen of Myanmar. Under the law, in order to obtain the most basic level (naturalized citizenship), they must proof that they have lived in Myanmar before 1948, as well as fluency in one of the national languages. Unfortunately, those requirements cannot be fulfilled by most of Rohingya people as they lack such paperwork because it was either unavailable or denied to them. As a result of such law, their rights to study, work, travel, marry, practice their religion and access health services have been continuously restricted. For these reasons, the Myanmar (formerly Burma) government shall repeal the 1982 Citizenship Law or abolish its over-burdensome requirements for citizens in a manner which has discriminatory effects on racial or ethnic minorities.